HLA-A SNPs and amino acid variants are associated with nasopharyngeal carcinoma in Malaysian Chinese - Yoon-Ming, Chin; Taisei, Mushiroda; Atsushi, Takahashi; Michiaki, Kubo; Gopala, Krishnan; Lee-Fah, Yap; Soo-Hwang, Teo; Paul Vey-Hong, Lim; Yoke-Yeow, Yap; Kin-Choo, Pua; Naoyuki, Kamatani; Yusuke, Nakamura; et al. (Wiley-Liss Inc., 2015)
Nasopharyngeal carcinoma (NPC) arises from the mucosal epithelium of the nasopharynx and is constantly associated with Epstein-Barr virus type 1 (EBV-1) infection. We carried out a genome-wide association study (GWAS) of 575,247 autosomal SNPs in 184 NPC patients and 236 healthy controls of Malaysian Chinese ethnicity. Potential association signals were replicated in a separate cohort of 260 NPC patients and 245 healthy controls. We confirmed the association of HLA-A to NPC with the strongest signal detected in rs3869062 (p=1.73 3 10-9). HLA-A fine mapping revealed associations in the amino acid variants as well as its corresponding SNPs in the antigen peptide binding groove (pHLA-A-aa-site-99=3.79 × 10-8, prs1136697=3.79 × 10-8) and T-cell receptor binding site (pHLA-A-aa-site-145=1.41 × 1024, prs1059520=1.41 × 10-4) of the HLA-A. We also detected strong association signals in the 50-UTR region with predicted active promoter states (prs41545520=7.91 × 10-8). SNP rs41545520 is a potential binding site for repressor ATF3, with increased binding affinity for rs41545520-G correlated with reduced HLA-A expression. Multivariate logistic regression diminished the effects of HLA-A amino acid variants and SNPs, indicating a correlation with the effects of HLA-A∗11:01, and to a lesser extent HLA-A∗02:07. We report the strong genetic influence of HLA-A on NPC susceptibility in the Malaysian Chinese. © 2014 UICC.